The teaching of the association between physical inactivity and non-communicable diseases in physical education classes - Julia Terra; Lúcio Canabarro; Marilda Neutzling; Nicole Gonzales; Airton Rombaldi (Revista Brasileira de Atividade Física e Saúde)
The study was conducted with physical education teachers from elementary and high schools in the urban area of Pelotas, southern Brazil, and identified the prevalence of those who taught the association of physical inactivity (PI) with non-communicable diseases (NCDs) during their classes. In addition, the moment when the content was discussed in the class and the length of time used for that purpose were investigated. We used a standardized questionnaire containing questions about the relationship between PI and NCDs, as well as information on demographic and socioeconomic aspects, career time, weekly labor hours and physical activity level. Overall, 188 teachers answered the census. Despite the high percentage of teachers who reported teaching at least one association between PI and NCDs (82.8%), obesity being the disease most frequently mentioned (84.7%), only 17.3% taught the association with cancer, 33% with osteoporosis and 11% of the teachers reported teaching the associations with all NCDs. As for obesity, the youngest age group (19-30 years) was the one that taught this association least frequently (p <0.001), with a reduction as their workload increased (p <0.03). A similar trend was observed regarding teaching the associations in the main part of the class (p <0.02) and the time devoted to teaching them in the main part of the class (p <0.006). Despite the high proportion of teachers who approached the associations between PI and NCDs during physical education classes, only the most disseminated associations by the media were taught by most teachers and by teachers with lower workloads. Health-related training activities should be offered to teachers, so that classes can include other contents beyond sports.